Annona emarginata (Schltdl.) H. Rainer 'araticum-de-terra-fria' cultivada com variação de nitrogênio: produtividade e perfil químico dos voláteis foliares - Campos, Felipe Girotto [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The species Annona emarginata (Schltdl.) H. Rainer 'araticum-de-terra-fria' has great potential as a rootstock for this hybrid atemoya (Annona cherimola Mill. X Annona squamosa L.) conferring resistance to stem borer. This resistance may be related to primary and secondary metabolisms. Nitrogen is an essential element on the synthesis of amino acids, proteins such as Ribulose 1,5 - diphosphate (Rubisco), nucleic acids, chlorophyll, secondary metabolites, and other important cellular constituents. Besides these functions, it should be considered competing relation to CO2 by reducing agents and carbon skeleton. Therefore, the present study aimed to evaluate the influence of variation in the level of nitrogen in the nutrient solution on yield and composition of the leaf volatile during the early development of seedlings of A. emarginata. To study the productivity gas exchange were evaluated, the activities of nitrate reductase, catalase, peroxidase, superoxide dismutase, lipid peroxidation, the dry weight of roots, stems and leaves, leaf area, stem diameter ratio leaf area, net assimilation rate, relative growth rate, leaf specific weight, dry weight distribution to different organs of the plant, leaf mass ratio and the composition of volatiles extracted from the leaves. Plants grown with intermediate levels of nitrogen had higher carboxylation efficiency and CO2 assimilation rate. Nitrate reductase activity varied with different levels of nitrogen that the plants were submitted. In the largest amount of nitrogen, plants with lower productivity, demonstrated competition between nitrogen fixation, CO2 assimilation and synthesis of terpenes. The activity of antioxidant enzymes prevented lipid peroxidation in plants subjected to different levels of nitrogen. Gas exchange, the activity of nitrate reductase and antioxidant enzymes in plants grown with 78.75 and 118.12 mg L-1 N contributed their best ...

A espécie Annona emarginata (Schltdl.) H. Rainer 'araticum-de-terra-fria' possui grande potencial como porta-enxerto para o híbrido atemoia (Annona cherimola Mill. x Annona squamosa L.), conferindo resistência contra a broca do tronco, característica dependente de seus metabolismos primário e secundário. O nitrogênio é um elemento essencial na síntese de aminoácidos, proteínas, entre elas, a Ribulose 1,5 - difosfato (Rubisco), ácidos nucleicos, clorofila e metabolitos secundários, entre outros importantes constituintes celulares. Além dessas funções, deve ser considerada sua relação de competição com o CO2 e síntese de terpenos, por agentes redutores e esqueletos carbônicos. Deste modo, o presente estudo objetivou avaliar a influência da variação do nível de nitrogênio na solução nutritiva, na produtividade e composição de voláteis foliares durante o desenvolvimento inicial de mudas de A. emarginata. Para o estudo da produtividade foram avaliadas as trocas gasosas, a atividade das enzimas nitrato redutase, catalase, peroxidade, superóxido dismutase, a peroxidação lipídica, a produção de massa seca de raiz, caule e folhas, área foliar, diâmetro de caule, razão de área foliar, taxa de assimilação líquida, taxa de crescimento relativo, peso específico de folhas, distribuição de massa seca para os diferentes órgãos do vegetal, razão de massa foliar e a composição de voláteis extraídos das folhas. As plantas cultivadas com níveis intermediários de nitrogênio apresentaram maior eficiência de carboxilação e taxa de assimilação de CO2. A atividade da nitrato redutase variou com os diferentes níveis de nitrogênio a que as plantas foram submetidas. No maior nível de nitrogênio utilizado, as plantas com menor produtividade, demostraram competição entre a fixação de nitrogênio, assimilação de CO2 e síntese de terpenos. A atividade das ...
Annona emarginata (Schltdl.) H. rainer 'araticum-de-terra-fria' cultivated with variation of nitrogen: yeld, chemical profile of volatile leaf
Keywords: Plantas - Transpiração; Anonacea; Terpenos; Plantas - Efeito do nitrogenio; Plants, Effect of nitrogen on